Cavernous sinus hemangioma: a rare entity - Vargas Urbina, John F. (2024)
Cavernous sinus hemangioma is considered as a vascular malformation or as a vascular tumor. It is usually extra-axially located, but it is histologically different from cavernomatous cerebral malformations. Clinical features may include headache, visual alterations or cranial nerve palsy. Diagnostic methods include CT scans, but the best is contrast-enhanced magnetic resonance imaging (MRI). Therapy may be microsurgery or radiotherapy. We present the case of a 30-year-old male, with no relevant past history, who had suffered with headache for three years, and diplopia for the last seven months, due to paresis affecting the sixth cranial nerve. Contrast-enhanced MRI showed an expansive lesion in the right cavernous sinus, with regular borders, T1 hypointense, with significant contrast uptake, T2 and FLAIR hyperintense, with no diffusion restriction. A craniotomy plus total resection of the tumor with hemostatic matrix support for controlling bleeding was performed. This patient developed complete ophthalmoparesis that improved over time. It was concluded that cavernous sinus hemangioma is an unusual condition, with high associated morbidity and mortality rates, but good results may be achieved with an adequate surgical technique.